The effect of reparixin on survival in patients at high risk for in-hospital mortality: a meta-analysis of randomized trials - Landoni, Giovanni; Zangrillo, Alberto; Piersanti, Gioia; Scquizzato, Tommaso; Piemonti, Lorenzo (Frontiers in Immunology, 2022)
Introduction: A great number of anti-inflammatory drugs have been suggested in the treatment of SARS-CoV-2 infection. Reparixin, a non-competitive allosteric inhibitor of the CXCL8 (IL-8) receptors C-X-C chemokine receptor type 1 (CXCR1) and C-X-C chemokine receptor type 2 (CXCR2), has already been tried out as a treatment in different critical settings. Due to the contrasting existing literature, we decided to perform the present meta-analysis of randomized controlled trials (RCTs) to investigate the effect of the use of reparixin on survival in patients at high risk for in-hospital mortality. Methods: We created a search strategy to include any human RCTs performed with reparixin utilization in patients at high risk for in-hospital mortality, excluding oncological patients. Two trained, independent authors searched PubMed, EMBASE, and the Cochrane Central Register of Controlled Trials (CENTRAL) for appropriate studies. Furthermore, references of review articles and included RCTs were screened to identify more studies. No language restrictions were enforced. To assess the risk of bias of included trials, the Revised Cochrane risk-of-bias tool for randomized trials (RoB 2) was used. Results: Overall, six studies were included and involved 406 patients (220 received reparixin and 186 received the comparator). The all-cause mortality in the reparixin group was significantly lower than in the control group [5/220 (2.3%) in the reparixin group vs. 12/186 (6.5%) in the control group, odds ratio=0.33 (95% confidence interval 0.12 to 0.96), p-value for effect 0.04, p for heterogeneity 0.20, I2=36%]. In addition, no difference in the rate of pneumonia, sepsis, or non-serious infections was shown between the two groups. Conclusion: Our meta-analysis of randomized trials suggests that short-term inhibition of CXCL8 activity improved survival in patients at high risk for in-hospital mortality without increasing the risk of infection. Meta-Analysis Registration: PROSPERO, identifier CRD 42021254467